A near-road modeling system for community-scale assessments of traffic-related air pollution in the United States. (April 2015) - Barzyk, Timothy M.; Isakov, Vlad; Arunachalam, Saravanan; Venkatram, Akula; Cook, Rich; Naess, Brian
Abstract: The Community Line Source (C-LINE) modeling system estimates emissions and dispersion of toxic air pollutants for roadways within the continental United States. It accesses publicly available traffic and meteorological datasets, and is optimized for use on community-sized areas (100–1000 km 2 ). The user is not required to provide input data, but can provide their own if desired. C-LINE is a modeling and visualization system that access inputs, performs calculations, visualizes results, provides options to manipulate input variables, and performs basic data analysis. C-LINE was applied to an area in Detroit, Michigan to demonstrate its use in an urban environment. It was developed in ArcGIS, but a prototype web version is in development for wide-scale use. C-LINE is not intended for regulatory applications. Its local-scale focus and ability to quickly (run time < 5 min) compare different roadway pollution scenarios supports community-based applications and help to identify areas for further research. Highlights: Developed a near-road modeling system to estimate mobile-source emissions and dispersion. The modeling system automatically provides nationwide coverage for most major roadways. Users can manipulate input data on traffic and meteorology to compare differences in resulting air toxics concentrations. The modeling system is optimized for use in local-scale community-based types of scenarios.